Climate crisis and human migration: the emergent sociolegal parameters of a science-based policymaking - Koskina, Anthi; Georgantas, Elias; Plionis, Manolis (Frontiers in Political Science, 2024)
IntroductionThe Paris Agreement, signed in 2015, is the epitome of the effort for a global consensus on the problem of climate change and its repercussions, including climate-induced migration, aimed at improving the institutional capacity for the formulation of effective adaptation and mitigation policies. One of its novel characteristics was the incorporation of science in the formal policy toolkit: States must use the best available science, as the empiricism of traditional policy-making regimes, bequeathed by an era of ordinary climatic patterns, must now take a backseat and give way to the emerging paradigm of science-based policymaking. Given the growing awareness of the climate migration problem affecting humans from all paths of life and likely to disrupt social cohesion and economic development, our era is set to become an epoch of climate migration; still, the rights of climate displaced peoples continue to be neglected.MethodsThis article examines the extent to which the Paris Agreement and associated public policies have the capacity to address climate induced migration, since international law urges States to address all critical impacts of climate change, using the best available scientific knowledge in this purpose. The analysis is based on a review of the existing literature on the science-policy interface, followed by a presentation of developing trends in international law. Subsequently, the authors attempt to present the socio-legal context of the emerging trends and assess the integration of science in climate migration policymaking. In this context, comparative case studies are presented to underscore what seems to be disparities and gaps in policy implementation in this area.ResultsOur findings show that climate change raises unforeseen challenges that have not been properly assessed by policy makers both at the international and national levels, such as the extent of climate-induced human displacement and migration and the urgent necessity for legal protection of climate-induced migrants. The lack of a concrete and legally binding framework for States is highlighted, while science is only incorporated at suboptimal levels, although there seem to be recent changes in this paradigm, suggesting a shift towards greater operational integration of scientific inputs.DiscussionThe study highlights the prospects and challenges of emerging policy contexts, especially the binding duty to use science for policymaking, resulting in specific obligations –i.e., the necessity to produce and disseminate data, and to create the necessary institutional arrangements–, given that existing policy measures remain inadequate in addressing the scale and urgency of climate induced migration. The incorporation of science in policy, although progressing, requires more robust implementation to support climate justice initiatives, that must be pursued despite the complex policy implications involved at all levels.ConclusionThe paper suggests that efforts must be intensified in this specific direction to efficiently support initiatives toward more social and environmental justice, such as encouraging the development of climate migration databases and establishing specialized bodies. Parallel to this, it is suggested that enhancing the role of scientific evidence in policymaking should go hand in hand with strengthening the international legal frameworks; both will be essential to ensure that climate-displaced populations are adequately protected and supported.